Prime-Boost Vaccination With Covaxin/BBV152 Induces Heightened Systemic Cytokine and Chemokine Responses - Kumar, Nathella Pavan; Banurekha, V. V.; C. P., Girish Kumar; Nancy, Arul; Padmapriyadarsini, C.; Mary, A. Stella; Devi, K. R. Uma; Murhekar, Manoj; Babu, Subash (Frontiers in Immunology, 2021)
Covaxin/BBV152 is a whole virion inactivated SARS-CoV-2 vaccine. The effect of prime-boost vaccination with Covaxin on systemic immune responses is not known. We investigated the effect of Covaxin on the plasma levels of a wide panel of cytokines and chemokines at baseline (M0) and at months 1 (M1), 2 (M2) and 3 (M3) following prime-boost vaccination in healthy volunteers. Our results demonstrate that Covaxin induces enhanced plasma levels of Type 1 cytokines (IFNγ, IL-2, TNFα), Type 2 /regulatory cytokines (IL-4, IL-5, IL-10 and IL-13), Type 17 cytokine (IL-17A), other pro-inflammatory cytokines (IL-6, IL-12, IL-1α, IL-1β) and other cytokines (IL-3 and IL-7) but diminished plasma levels of IL-25, IL-33, GM-CSF and Type 1 IFNs. Covaxin also induced enhanced plasma levels of CC chemokine (CCL4) and CXC chemokines (CXCL1, CXCL2 and CX3CL1) but diminished levels of CXCL10. Covaxin vaccination induces enhanced cytokine and chemokine responses as early as month 1, following prime-boost vaccination, indicating robust activation of innate and adaptive immune responses in vaccine recipients.